Effectiveness Of Active Learning Method Quiz Team Type On Student Learning Outcomes In Subject Ohm Law In SMA Negeri 1 Pundong - Abu Yazid Raisal; Nanang Suwondo (Indonesian Review of Physics (IRiP), 2018)
This study aims to measure the increase in student learning outcomes from cognitive aspects and student activity between active quiz type learning methods and conventional methods. The sampling technique is non-random sampling. Data was collected using the pre-test and post-test for cognitive aspects while the affective aspects used the observation. Analysis of the data used the normality test, homogeneity test, and hypothesis testing. The hypothesis test used is a two-party t test. The results show that tcount= 7.273 > ttable= 2.01 at a significant level of 5%. It means that there are significant differences for cognitive aspects between learning outcomes using the team quiz type and conventional methods of active learning methods. Overall the team quiz method is more effective for improving student learning outcomes from cognitive aspects, and student activities.